PENERAPAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN DARING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA DI SMP NEGERI 1 SIDOARJO - Anita Desy Rochmadona; Tutut Nurita (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This study aims to describe the discovery learning model during online learning in improving students' science process skills. This research used pre-experimental design with a research draft of one group pretest-posttest. This study used two class subjects, namely class VII-C as many as 30 students and class VII-D as many as 30 students which is conducted at SMP Negeri 1 Sidoarjo. The data collection technique in the form of description questions test was related to science process skills which is given before and after learning. It showed that there is an increase in the completeness of science process skills, the percentage and the n-gain on each indicator of science process skills, as well as the n-gain test on the results of the pretest and posttest in both classes with the high category. The n-gain result in VII-C class was 0.77, while VII-D class was 0.79. Therefore, based on the data above, it can be concluded that the discovery learning model during online learning can improve science process skills.